2022
DOI: 10.3390/nu14071482
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Palmitoleic Acid in Regulating Hepatic Gluconeogenesis through SIRT3 in Obese Mice

Abstract: Hepatic gluconeogenesis is a crucial process to maintain glucose level during starvation. However, unabated glucose production in diabetic patients is a major contributor to hyperglycemia. Palmitoleic acid is a monounsaturated fatty acid (16:1n7) that is available from dietary sources. Palmitoleic acid exhibits health beneficial effects on diabetes, insulin resistance, inflammation, and metabolic syndrome. However, the mechanism by which palmitoleate reduces blood glucose is still unclear. SIRT3 is a key metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Another explanation is that the high-fat diet Relative mRNA levels supplemented with high fructose/glucose in drinking water might suppress PCK1 expression 34 . Under a high-fat diet, PA decreased PCK1 expression via SIRT3 inhibition 35 . Additionally, acetylation, ubiquitination, and phosphorylation modulate PCK1 expression 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that the high-fat diet Relative mRNA levels supplemented with high fructose/glucose in drinking water might suppress PCK1 expression 34 . Under a high-fat diet, PA decreased PCK1 expression via SIRT3 inhibition 35 . Additionally, acetylation, ubiquitination, and phosphorylation modulate PCK1 expression 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Through sequencing, we screened MDH2 as a target for deacetylation by SIRT3, and in combination with IP experiments, we demonstrated that Sirt3 directly deacetylates MDH2. Hence, SIRT3 is able to directly communicate and alter the acetylation level of MDH2 (60,61) . Our research confirms this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Lysates prepared from frozen liver samples were used for western blot. The level of phospho-NF-κB p65 (Ser536) (Cell Signaling Technology, #3033), NFκB p65 (Cell Signaling Technology, #8214), the stress-activated protein kinase/Jun-amino-terminal kinase (SAPK/JNK) (Cell Signaling Technology, #9252), phospho-SAPK/JNK(Thr183/Thr185) (Cell Signaling Technology, #9251), IL-1β (Cell Signaling Technology, #12242), Phospho-p38 MAPK (Thr180/Tyr182) (Cell Signaling Technology, #4511), p38 MAPK (Cell Signaling Technology, #8690), FGF21 (Affinity Biosciences, #DF8947), Collagen 1 a 1 (Santa Cruz Biotechnology, # sc-293182),Collagen 3 a 1 (Santa Cruz Biotechnology, #sc-271249), Smooth muscle ac-tin (Santa Cruz Biotechnology, #sc-53142) and Tubulin (Cell Signaling Technology, #2125) were analyzed as described ( 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%